Bioremediation of direct dyes in simulated textile effluents by a paramorphogenic form of Aspergillus oryzae - Corso, C. R. [UNESP]; Almeida, E. J. R. [UNESP]; Santos, G. C. [UNESP]; Morao, L. G. [UNESP]; Fabris, G. S. L. [UNESP]; Mitter, E. K. [UNESP] (I W A Publishing, 2012)
Azo dyes are extensively used for coloring textiles, paper, food, leather, drinks, pharmaceutical products, cosmetics and inks. The textile industry consumes the largest amount of azo dyes, and it is estimated that approximately 10-15% of dyes used for coloring textiles may be lost in waste streams. Almost all azo dyes are synthetic and resist biodegradation, however, they can readily be reduced by a number of chemical and biological reducing systems. Biological treatment has advantages over physical and chemical methods due to lower costs and minimal environmental effect. This research focuses on the utilization of Aspergillus oryzae to remove some types of azo dyes from aqueous solutions. The fungus, physically induced in its paramorphogenic form (called 'pellets'), was used in the dye biosorption studies with both non-autoclaved and autoclaved hyphae, at different pH values. The goals were the removal of dyes by biosorption and the decrease of their toxicity. The dyes used were Direct Red 23 and Direct Violet 51. Their spectral stability (325-700 nm) was analyzed at different pH values (2.50, 4.50 and 6.50). The best biosorptive pH value and the toxicity limit, (which is given by the lethal concentration (LC100), were then determined. Each dye showed the same spectrum at different pH values. The best biosorptive pH was 2.50, for both non-autoclaved and autoclaved hyphae of A. oryzae. The toxicity level of the dyes was determined using the Trimmed Spearman-Karber Method, with Daphnia similis in all bioassays. The Direct Violet 51 (LC100 400 mg . mL(-1)) was found to be the most toxic dye, followed by the Direct Red 23 (LC100 900 mg . mL(-1)). The toxicity bioassays for each dye have shown that it is possible to decrease the toxicity level to zero by adding a small quantity of biomass from A. oryzae in its paramorphogenic form. The autoclaved biomass had a higher biosorptive capacity for the dye than the non-autoclaved biomass. The results show that bioremediation occurs with A. oryzae in its paramorphogenic form, and it can be used as a biosorptive substrate for treatment of industrial waste water containing azo dyes.
Keywords: Aspergillus oryzae; azo dye; bioremediation; biosorption; Daphnia similis; paramorphogenic form; toxicity